P591 The effect of hormonal contraception on the vaginal microbiota over 2 years. (14th July 2019) - Tuddenham, Susan; Ghanem, Khalil; Gajer, Pawel; Robinson, Courtney; Ravel, Jacques; Brotman, Rebecca
Abstract : Background: Despite widespread use, the effect of hormonal contraception (HC) on the vaginal microbiota (VMB) is understudied. We compared VMB in a longitudinal observational study of women during intervals on and off HC. Methods: Women stopping and starting any form of HC and women off HC (controls) collected vaginal swabs twice-weekly for 2 weeks prior to 7 study visits over 2 years. 16S rRNA gene sequencing was conducted, and the VMB was categorized into 7 community state types (CSTs): 4 dominated by Lactobacillus spp, and 3 by Streptococcus spp (CST VI), Bifidobacterium spp (CST VII), or a variety of anaerobes (CST IV). Mixed effects logistic regression models assessed differences in CST proportions. Bayesian double exponential random effects models estimated differences between stability indices within HC and control subjects (measured by median Jensen-Shannon distance [MJSD] from the subject's own centroid and from the centroid of CST I [ L. crispatus- dominated]). Results: 4185 samples from 105 women (73 HC, 32 controls) were available for analysis. The VMB was more stable in women on HC as compared to controls (MJSD 0.16 vs 0.22, p<0.01) and in oral contraceptive pill users versus controls (MJSD 0.14 vs 0.22, p<0.01). Women had increased stability after being on HC for ≥3 months as compared to <3 months (MJSD difference −0.43, p<0.01). Women on HC for ≥3 months were more likely to be in CST I (51.3% vs 37.3%, p<0.01) and less likely to be in CST IV (11.4% vs 22.5%, p=0.01) than controls. Women on HC ≥3 months maintained VMB closer to CST I than controls (MJSD 0.21 vs 0.42, p<0.01). Conclusion: Women on HC have more stable, Lactobacillus -dominated VMB than controls. There is increased VMB stability after 3 months of HC use. Further assessment by HC type is currently being integrated into the analysis. Disclosure: No significant relationships.